Effects of Thinning Intensity on Growth of 27-year-old Slash Pine (Pinus elliottii) in Northern Iran - Bonyad, Amir (Indian Forester, 2007)
Slash pine (Pinus elliottii) is one of the main exotic species, commercially planted in Northern Iran. The Caspian forests of Iran are located in the southern border of the Caspian Sea and cover an area of 1.9 million ha. Unthinned, light thinned and moderate thinned stands were three study populations. Data were collected from 150 trees with different stand density. For basal area analysis, 84 plots were measured. Variables such as diameter at breast height (dbh), total height, tree volume, bark thickness, basal area per hectare, crown length, and crown diameter were measured. Growth rate ratios of dbh in light and moderate thinned stands were 1.081 and 1.15 respectively. MAI of basal area growth rates were 1.12 and 1.15 in two thinned populations. Moderate thinning increased about 6.20% stand volume. After thinning, dimensions of crowns became greater and more branches were evident. Percentages of live crown ratios in three study populations were calculated as 29.69%, 30.39% and 30.66%. Growth rates analysis were supported by statistical multivariate analysis of variance using Wilk's (Î›) and Hotelling's T22 tests. The Wilk's test (Î›) was carried out on mean vector of 6 variables (p=6) with three (k=3) study populations. Null hypothesis (H0) was rejected at level of Î± = 0.001. The results indicated that moderate thinning was highly significant affected on rapid growth rates of planted Slash pine stands.